2019
DOI: 10.1364/ol.44.000843
|View full text |Cite
|
Sign up to set email alerts
|

Ultrashort infrared 25–11  μm pulses: spatiotemporal profiles and absolute nonlinear response of air constituents

Abstract: We measure the detailed spatiotemporal profiles of femtosecond laser pulses in the infrared wavelength range = . − , and the absolute nonlinear response of major air constituents (N2, O2, and Ar) over this range. The spatiotemporal measurements reveal wavelength-dependent pulse front tilt and temporal stretching in the infrared pulses.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Figure 5a shows that Eq. (6) provides a very good fit for the experimental data obtained by Zahedpour et al 62,63 and confirms the flat and featureless landscape of air n 2K dispersion at mid-infrared and farinfrared wavelengths. Additionally, Brown et al 64 found that over the wavelength range of 2-4 μm, the Kerr nonlinear index n 2K of air is insensitive to the laser intensity up to intensities as high as 10 14 W/cm 2 (though at shorter wavelengths, a weak intensity dependence, caused by nonnegligible ionization, was observed for intensities above 5 × 10 13 W/ cm 2 ).…”
Section: Nonlinear Polarization: Kerr and Raman Effectssupporting
confidence: 79%
See 3 more Smart Citations
“…Figure 5a shows that Eq. (6) provides a very good fit for the experimental data obtained by Zahedpour et al 62,63 and confirms the flat and featureless landscape of air n 2K dispersion at mid-infrared and farinfrared wavelengths. Additionally, Brown et al 64 found that over the wavelength range of 2-4 μm, the Kerr nonlinear index n 2K of air is insensitive to the laser intensity up to intensities as high as 10 14 W/cm 2 (though at shorter wavelengths, a weak intensity dependence, caused by nonnegligible ionization, was observed for intensities above 5 × 10 13 W/ cm 2 ).…”
Section: Nonlinear Polarization: Kerr and Raman Effectssupporting
confidence: 79%
“…While the values of the Kerr nonlinear index n 2K for air have been measured for various wavelengths, from the ultraviolet up to the near-infrared parts of the spectrum, until recently, there were no corresponding data for the midinfrared and far-infrared spectral range. Currently, the most comprehensive measurements of n 2K for different air constituents were made by Zahedpour et al 62,63 using the single-shot supercontinuum spectral interferometry technique. They presented the experimental values of the Kerr nonlinear index for nitrogen and oxygen in a very wide range of wavelengths from 0.4 to 11 μm.…”
Section: Nonlinear Polarization: Kerr and Raman Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have found that the rovibrational nonlinearity of CO 2 is dominated by the resonant ac-Stark or power broadening effect and that the sign of the nonlinearity is opposite to that predicted by the commonly used two-level system model that describes the resonant nonlinear optics of both atoms and molecules in the gas phase [14]. We determine that the nonlinear refractive index of low-pressure CO 2 is ~ 10 -12 cm 2 /W suggesting that the 400 ppm CO 2 concentration can act to increase the nonlinear refractive index of ambient air by four orders of magnitude as compared to the non-resonant values measured in the midand LWIR [15][16][17][18].…”
Section: Introductionmentioning
confidence: 76%